The World Wide Web Conference 2019
DOI: 10.1145/3308558.3313633
|View full text |Cite
|
Sign up to set email alerts
|

The Block Point Process Model for Continuous-time Event-based Dynamic Networks

Abstract: We consider the problem of analyzing timestamped relational events between a set of entities, such as messages between users of an on-line social network. Such data are often analyzed using static or discrete-time network models, which discard a significant amount of information by aggregating events over time to form network snapshots. In this paper, we introduce a block point process model (BPPM) for continuous-time event-based dynamic networks. The BPPM is inspired by the well-known stochastic block model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Less common, but potentially useful, theory-based models define edge dynamics, for example as generative network models [93]. These models could be profitably extended by recently developed dynamic extensions of the classic random graph, including the configuration model, the stochastic block model, and the block-point process model [94,95].…”
Section: From Data Representation To First-principles Theorymentioning
confidence: 99%
“…Less common, but potentially useful, theory-based models define edge dynamics, for example as generative network models [93]. These models could be profitably extended by recently developed dynamic extensions of the classic random graph, including the configuration model, the stochastic block model, and the block-point process model [94,95].…”
Section: From Data Representation To First-principles Theorymentioning
confidence: 99%
“…Users interact sequentially with items in many domains such as e-commerce (e.g., a customer purchasing an item) [48], education (a student enrolling in a MOOC course) [31], and social and collaborative platforms (a user posting in a group in Reddit) [19, 24]. The same user may interact with different items over a period of time and these interactions change over time [4, 5, 17, 21, 34, 37, 48]. These interactions create a network of temporal interactions between users and items .…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners then inspect fitted parameters to understand inherent temporal dependencies, and perform downstream tasks such as prediction via simulation of the fitted processes [15], [17]. As inferring and interpreting (all) fitted Hawkes process parameters is crucial in many real-world applications [3], [6], [17]- [20], [22], we turn our attention to the challenges in fitting Hawkes process parameters, and especially, in estimating the decay parameter in the exponential kernel. Previous research has shown that the baseline µ and excitation jump α can be efficiently computed since the log-likelihood is amenable for convex optimization of these parameters [5], [18].…”
Section: B Decay Estimationmentioning
confidence: 99%
“…We begin by addressing the problem of quantifying the uncertainty of fitted decay values β, as well as potential consequences of mis-estimation on other Hawkes process parameters. One prominent application of multi-dimensional Hawkes processes consists in the estimation of directions of temporal dependency, e.g., when studying influence in online communities [17], [20], or in approximating complex geographical [3] or cortical [21] relationships. Recall that inferring such relations between a pair of Hawkes process dimensions may be framed as a problem of estimating which cross-excitation between the two dimensions is higher.…”
Section: A Quantifying the Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation